2012
DOI: 10.1161/strokeaha.111.646943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Telerehabilitation on Physical Function and Disability for Stroke Patients

Abstract: Background and Purpose— To determine the effect of a multifaceted stroke telerehabilitation (STeleR) intervention on physical function, and secondarily on disability, in veterans poststroke. Methods— We conducted a prospective, randomized, multisite, single-blinded trial in 52 veterans with stroke from 3 Veterans Affairs medical centers. Veterans with a stroke in the preceding 24 months were randomized to the STeleR intervention or usual care. The STele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
200
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(213 citation statements)
references
References 22 publications
3
200
0
10
Order By: Relevance
“…It can also serve as an alternative to "homecare" rehabilitation, which requires the treating therapist or clinician to travel to the patient's home. By reducing or eliminating barriers relating to travel time and travel-related costs, telerehabilitation has the potential to improve access to rehabilitative care for stroke survivors [6][7]. Improving access to rehabilitative care may reduce disparities for stroke survivors and caregivers facing financial or transportation-related challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also serve as an alternative to "homecare" rehabilitation, which requires the treating therapist or clinician to travel to the patient's home. By reducing or eliminating barriers relating to travel time and travel-related costs, telerehabilitation has the potential to improve access to rehabilitative care for stroke survivors [6][7]. Improving access to rehabilitative care may reduce disparities for stroke survivors and caregivers facing financial or transportation-related challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Improving access to rehabilitative care may reduce disparities for stroke survivors and caregivers facing financial or transportation-related challenges. While research on telerehabilitation is limited, there is increasing evidence supporting the need for telerehabilitation services, the development of telerehabilitation interventions, and support for people with disabling conditions that potentially limit access to rehabilitation services [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Telerehabilitation is an emerging method of rehabilitation that consists of the remote delivery and monitoring of rehabilitation services (McCue, Fairman, & Pramuka, 2010) and has the potential to provide health care services to underserved areas with potential cost and travel savings (Chumbler et al, 2010;Gamble, Savage, & Icenogle, 2004). Several studies have supported the efficacy of telerehabilitation in facilitating motor recovery and activities of daily living (ADL) performance after stroke (Chumbler et al, 2012;Lum, Uswatte, Taub, Hardin, & Mark, 2006;Rogante, Grigioni, Cordella, & Giacomozzi, 2010); however, the research devoted to telerehabilitation and QOL outcomes has been limited.…”
mentioning
confidence: 99%
“…Technology applications such as telehealth, which is the use of electronic information and telecommunication technologies to facilitate long-distance clinical healthcare and patient related education [18], provides a promising option for providing this support [19]. While others have reported on telehealth applications, none, to our knowledge, have reported the use of tele-rehabilitation to promote exercise adherence and progression in people with post stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a randomized controlled trial, Chumbler et al [19] reported improved physical function in Veterans participating in a post-stroke tele-rehabilitation program (STeleR) which included instruction for functionally-based exercises and adaptive strategies. The authors concluded that the STeleR program might be a useful supplement to traditional post-stroke in-home care [19].…”
Section: Introductionmentioning
confidence: 99%